Recovery of vanished URLs: Comparing the efficiency of Internet Archive and Google - Kumar, D. Vinay; Sampath Kumar, B. T. (Malaysian Journal of Library and Information Science, 2017)
This article examines the vanishing nature of URLs and recovery of vanished URLs through Internet Archive and Google search engine. For that purpose study investigates the URLs cited in the articles of two LIS journals published during 2009-2013. A total of 226 articles published in two open access LIS journals were selected. Of 5197 citations cited in 226 articles, 21.05 percent were URLs (1094). Study found that 38.12 percent (417 out of 5197) URLs were found missing and remaining 61.88 percent of URLs were active at the time of URL check with W3C link checker. The HTTP 404 error message – “page not found” was the overwhelming message encountered and represented 54.2 percent of all HTTP error message. Internet Archive and Google search engine were used to recover vanished URLs. However, the Internet Archive recovered 66.19 percent of the total vanished URLs, whereas, Google manages to recover only 30.70 percent of the total vanished URLs. The recovery of vanishing URLs through Internet Archive and Google increased the active URL’s rate from 61.88 per cent to 87.11 per cent and 73.58 per cent respectively. Study found that Internet Archive is a most efficient tool to recover vanished URLs compared to Google search engine.